Body satisfaction and use anabolic steroids perceptions of adolescents - Oliveira, Ubirajara de; Bocalini, Danilo Sales; Filho, José Martins (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Background: It is known that adolescence is a phase of transformation subject to innumerable influences. Objective: The objective of this study was to identify the level of body satisfaction among male adolescents practicing bodybuilding and perception and value attributed to the use of anabolic steroids (AS). Methods: The sample consisted of 3150 male adolescents aged 15 to 21 years. The adolescents were submitted to a questionnaire with 41 questions containing several elements detected such as: the level of body satisfaction, the bodybuilding practice proposing body changes and the possible use of AS. Results: The main results were attributed to the high level of satisfaction for body image variables from the members of their social group in 1883 (60%, X2 = 26.361; p<0.005), body mass 1552 (50%; X2 = 55.374; p<0.005) and muscle mass 1199 (39%, X2 = 10.405; p <0.005). Additionally, 1243 (39%; X2 = 31.926; p <0.005) adolescents confirm the possibility of use; the preference for faster means to achieve changes in their bodies, even knowing about health risks was 1347 (43%; X2 = 31.926; p<0.005). On the knowledge of the effects to the point of refusing their involvement related to the use of AS with aesthetic objectives 1152 (36%; X2 = 45.758; p<0.005) students affirm that they did not know, however, they would still use it, with statistically significant observed differences. Conclusion: Although it is possible to consider a high level of satisfaction for the variables associated with body image, adolescents consider the use of AS to achieve changes in their bodies by faster means, despite knowing about health risks even without knowledge of the effects related to the use of AS for aesthetic purposes.